Market distance and household income: Quasi-experimental evidence from Mongolia - Tseveenjav Lkhanaa (Graduate Institute of International and Development Studies, 2024)
This paper examines the impact of access to markets on livestock-related income of herder households in Mongolia. The empirical findings show that reducing the distance to markets by ten kilometers increases household income by 1.0 percent on average.
Keywords: I30; O12; O18; Q12; R3; 330; access to markets; market distance; rural poverty; rural household income; herder household income; household location